Enhanced low-temperature NH3-SCR performance of Ce/TiO2 modified by Ho catalyst - Ting-ting Zhang (Royal Society Open Science, 2019)
Holmium was used as a dopant to boost the low-temperature NH3-selective catalytic reduction (SCR) performance of Ce/TiO2 catalyst. It was ascertained that certain amount of Ho-doping species could exceedingly improve the low-temperature SCR activity under 60 000 h−1 of Ce/TiO2, accompanied with the improvement of tolerance to H2O and SO2 at 200°C. Characterization results manifested that Ho modification could not only result in inhibiting the growth of TiO2 crystals and the enlargement of specific surface area but also lead to the enhanced redox ability and the increased amount of surface-adsorbed substances, all of which could promote the low-temperature NH3-SCR performance of Ce/TiO2.